2022
DOI: 10.3390/polym14214742
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Mechanical and Physical Properties of Glass/Jute Hybrid Laminates

Abstract: Natural fibres have been partly substituting synthetic fibres in polymer composites due to their renewable character and many other advantages, and sometimes, they can be hybridized into a single composite for a better combination of properties. This work aims to study the effect of hybridization and stacking sequence on the mechanical and physical properties of the glass/jute laminates. For that, pure jute, pure glass and glass/jute hybrids were manufactured by vacuum infusion process using orthophthalic poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Conversely, laminates containing glass exhibit longer burn times, particularly on their faces, due to the inorganic nature of glass. Composed of 70-75% silica (SiO 2 ), sodium carbonate, and calcium carbonate, glass offers greater resistance to fire exposure [12]. The similarity between the reference polyester and G5 can be explained by the high permeability of glass mats during infusion, which can facilitate the flow of resin through fiberglass mats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, laminates containing glass exhibit longer burn times, particularly on their faces, due to the inorganic nature of glass. Composed of 70-75% silica (SiO 2 ), sodium carbonate, and calcium carbonate, glass offers greater resistance to fire exposure [12]. The similarity between the reference polyester and G5 can be explained by the high permeability of glass mats during infusion, which can facilitate the flow of resin through fiberglass mats.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Acosta et al [13] proposed the use of balsa wood veneers as an alternative material that has a higher-volume production and lower cost (depending on the region) compared to other fibers (e.g., jute, sisal, ramie, etc. ), and in a later study [14] the same authors proposed, due to the excellent physical and mechanical properties found in the previous work, the hybridization of pine wood veneers with glass mats and jute fabrics, as an even more economically viable alternative to other types of plant fibers, producing laminates with a physical and mechanical performance notoriously superior even to other types of hybrid laminates using natural fibers [10,12]. Although this is nothing completely new in the literature, these laminates using glass have already been well explored from the point of view of mechanical and physical properties.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The SEM images also showed the heterogeneous fiber architecture commonly found in natural fibers (red circle in Figure 5 ), which hinders resin flow through fiber fabric, leading to the formation of voids filled with entrapped air [ 34 ]. Acosta et al [ 22 ], who manufactured wood–jute laminates using the vacuum infusion process, also ascribed the high void content to the presence of jute fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…Both in terms of research and application, interest in advanced materials is growing quickly. They are used in the manufacturing of bicycles, sports equipment, machinery, devices, engineering solutions, and biological wastewater treatment technologies, among other industries[6] [7]. This study's goal is to increase the need for mitigating the negative environmental effects of synthetic bers and polymers, encourage the use of natural materials, and focus research efforts on the creation of biodegradable systems [8].…”
Section: Introductionmentioning
confidence: 99%